2010
DOI: 10.1309/ajcpg0mnr5ngknfx
|View full text |Cite
|
Sign up to set email alerts
|

Platelet Factor 4/Heparin Antibodies in Blood Bank Donors

Abstract: Platelet factor 4 (PF4)/heparin antibody, typically associated with heparin therapy, is reported in some heparin-naive people. Seroprevalence in the general population, however, remains unclear. We prospectively evaluated PF4/heparin antibody in approximately 4,000 blood bank donors using a commercial enzyme-linked immunosorbent assay for initial and then repeated (confirmatory) testing. Antibody was detected initially in 249 (6.6%; 95% confidence interval [CI], 5.8%-7.4%) of 3,795 donors and repeatedly in 163… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
63
1
4

Year Published

2011
2011
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(72 citation statements)
references
References 30 publications
4
63
1
4
Order By: Relevance
“…We and others have also shown that normal individuals have anti-PF4/heparin antibodies in their plasma, 10 likely induced by minor bacterial inflammation, such as periodontal disease. Under normal conditions, the pathologic-activating capacities of these antibodies are likely quenched by scavengers but when the capacity of these proposed scavengers is overloaded, for example, after major surgery and treatment with heparin, strong activation of platelets, monocytes, and endothelial cells result in a prothrombotic situation.…”
mentioning
confidence: 57%
“…We and others have also shown that normal individuals have anti-PF4/heparin antibodies in their plasma, 10 likely induced by minor bacterial inflammation, such as periodontal disease. Under normal conditions, the pathologic-activating capacities of these antibodies are likely quenched by scavengers but when the capacity of these proposed scavengers is overloaded, for example, after major surgery and treatment with heparin, strong activation of platelets, monocytes, and endothelial cells result in a prothrombotic situation.…”
mentioning
confidence: 57%
“…5,12 These antibodies are highly significantly associated with periodontitis, one of the most prevalent human infections, often associated with transient bacteremia. 13 The major bacterial species in periodontitis are the Gram-negative bacteria Aggregatibacter actinomycetemcomitans and Porphyromonas gingivalis.…”
Section: Introductionmentioning
confidence: 99%
“…11,12 Furthermore, preimmunization by sepsis could not explain the presence of naturally occurring anti-PF4/heparin Abs in 3%-8% of the normal population. 6,10,13 We hypothesized that periodontitis might be a cause of preimmunization to PF4/heparin complexes. Periodontitis is one of the most prevalent human infections.…”
Section: Introductionmentioning
confidence: 99%